Development of A Physical Simulation Game in Global Supply Chain Issues - Hafizah Hamka, Farah; Saibani, Nizaroyani; Nizam Ab Rahman, Mohd; Harun, Zambri; Hishamuddin, Hawa (International Journal of Engineering and Technology, 2019)
Development of a physical simulation game is an interactive method that can be used in the theoretical understanding of the global supply chain management, for academicians and also for industry practitioners. In this study, there are three objectives to be achieved, namely to identify the importance of supply chain game in understanding the theory of global supply chain, to develop a supply chain game with physical simulation method and to identify the effectiveness of the game to understand the theory of global supply chain. A physical simulation game then was designed and conducted among a group of university students. To facilitate researchers to obtain information, a questionnaire survey conducted on the participants before and after the game. There are two purposes of this survey, which is carried out to determine the participants' understanding about the theory of global supply chains and to identify the effectiveness of this physical simulation game. Regarding on the survey results, nearly 50% mean average response of the participants increased significantly was recorded. It shows that there is an increase understanding of the students about the given theory throughout this physical simulation game.Â Â